Edgar Lee Masters papers - Masters, Edgar Lee, 1868-1950.
Typescript autobiography with holograph corrections for publication by David Karsner in the New York Herald Tribune and a related TLS (1926 October 15) from Masters to Karsner; and a signed holograph copy of the poem titled Anne Rutledge (published in the Spoon River Anthology, 1915; copy, 1941) and TLS (1939 February 14) from Masters to Sherman Day Wakefield concerning Anne (Ann) Rutledge and Abraham Lincoln.
Author and poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Karsner, David, -- 1889-1941 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Rutledge, Ann, -- -1835.; Wakefield, Sherman Day, -- 1894-1971 -- Correspondence; American poetry; Authors; Poets